Differential Screening of Randomly Amplified cDNAs Using RAPD Primers in Salt Tolerance and Sensitive Wheat - Sabbah, Majeed A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The identification of salinity-tolerance genes is a critical aspect of the new molecular technology. In this work cDNA-RAPD is used for the identification of genes expressed in salt tolerant but not in salt sensitive wheat. Two cultivars wheat, salt tolerance (Dijla) and sensitive (Tamooz2) were used for the preparation of RNA and cDNA synthesis. Eight primers were used for random amplification of cDNA constructed from RNA and three primers were differentially expressed in salt tolerant cultivars. Genes related to salt tolerant were predicted using NCBI blast for the three primers. The predicted genes were involved in salt tolerance of wheat and other plants as well. This indicates the suitability of the primers and the method for salt tolerance genes identification in wheat under study.